Systematic Literature Review: Opportunities and Strategies for Implementing Artificial Intelligence in Chemistry Learning in Indonesia - Priyadi*, Danang; Widjajanti, Endang; Kamari, Azlan (Universitas Syiah Kuala, 2025)
There are major changes in industrial structure where digitalization and technological innovation are becoming the main factors of economic growth.This research aims to identify opportunities and strategies in the application of artificial intelligence (AI) to enhance chemistry learning in Indonesia. Through the systematic literature review (SLR) method, this research reviews 33 journals related to the application of AI in education, particularly in the subject of chemistry. Analysis shows that AI has the potential to make a significant impact through a more personalized, interactive, and adaptive approach to student needs. In addition, AI offers solutions to learning challenges, such as limited laboratory infrastructure, through the use of virtual simulations that facilitate experimental practice. Strategies that support the implementation of AI in chemistry education in Indonesia include improving access to technology, continuous teacher training, and raising awareness of technological changes in education. With effective implementation, AI is expected to make a real contribution to improving the quality of chemistry education in Indonesia